IMPLEMENTASI e-GOVERNMENT PADA PELAYANAN DAN PENGAWASAN OLEH DIREKTORAT JENDERAL IMIGRASI DALAM UPAYA KETAHANAN NASIONAL: ANALISIS STRATEGI DAN TANTANGAN - Helistiawan, Anton; Sartika, Ika (Polteknik Imigrasi, 2025)
Abstract. This study explores the implementation of e-Government in immigration services and supervision by the Directorate General of Immigration of Indonesia, particularly through systems such as immigration technology and management System. Within the framework of national resilience and digital transformation, this qualitative case study analyzes the effectiveness of digital systems, structural challenges, and the implications for the principle of digital sovereignty. The findings indicate that digitalization has enhanced service efficiency and immigration oversight but faces challenges including infrastructure disparity, dependency on foreign vendors, bureaucratic resistance, and limited inter-agency integration. The study recommends adopting the sovereignty-by-design principle, strengthening sovereign capacity building, and developing a Sovereign Interoperability Gateway to ensure a resilient, sovereign, and inclusive immigration digital transformation as a foundation for national resilience in the digital age. Keywords: e-Government; digital sovereignty; immigration supervision; national resilience